Altered functional connectivity and hyperactivity of the caudal hippocampus in schizophrenia compared with bipolar disorder: a resting state fMRI (functional magnetic resonance imaging) study - Li Zhang; Wenli Wang; Yuan Ruan; Zhiyong Li; Le Sun; Gong-Jun Ji; Yanghua Tian; Kai Wang (BMC Psychiatry)
Abstract Background Schizophrenia patients frequently present with structural and functional abnormalities of the hippocampus (Hipp). Further, these abnormalities are often associated with specific symptom profiles. Aim To determine whether schizophrenia patients show specific functional connectivity (FC) and activity abnormalities in each hippocampal subregion compared to the BD (bipolar disorder) and HC (healthy control) groups. Methods Basal activation state and functional connectivity (FC) in four subregions of the bilateral Hipp were examined: left caudal (cHipp_L), right caudal (cHipp_R), left rostral (rHipp_L), and right rostral (rHipp_R). Resting-state functional magnetic resonance images were obtained from 62 schizophrenia patients, 57 bipolar disorder (BD) patients, and 45 healthy controls (HCs), and analyzed for fractional amplitude of low-frequency fluctuations (fALFF) as a measure of basal neural activity and for whole-brain FC based on the hippocampal subregions. Results The schizophrenia group exhibited greater fALFF in bilateral cHipp (the caudal part of hippocampus) and rHipp (the rostral part of hippocampus) subregions compared to BD and HC groups as well as increased FC between the bilateral cHipp and multiple brain regions, including the thalamus, putamen, middle frontal gyrus, parietal cortex, and precuneus. Moreover, fALFF values of the bilateral cHipp were positively correlated with the severity of clinical symptoms as measured by the Positive and Negative Syndrome Scale. Conclusions These findings confirm an important contribution of hippocampal dysfunction, especially of the cHipp, in schizophrenia. Further, hyper-connectivity and hyperactivity of the cHipp could serve as a biomarker for therapeutic development.